A new species of Siphoneugena and a new combination in Plinia (Myrtaceae) - Caldas, Diana K.d.; Stadnik, Aline M.s.; Souza, Marcelo Da C.; Rosário, Alessandro S. Do; Baumgratz, José Fernando A. (Phytotaxa, 2025)
Siphoneugena itatiaiensis, endemic to the Itatiaia National Park, in the Brazilian southeastern state of Rio de Janeiro, is proposed as a new species, and is described and illustrated. This new species is morphologically close to S. densiflora, but differs by the combination of oblong leaf blades, pilose flowers with hypanthium not constricted above the ovary, and ovaries with 3 ovules per locule. Additionally, there is proposed, for the southeastern Brazilian species until now named Plinia anonyma, the new combination Plinia sulcata, based in Paramitranthes sulcata.